HRM PRACTICES ACROSS DIFFERENT CULTURES: AN EVIDENCE-BASED STUDY IN NETHERLANDS AND SOUTH AFRICA - Nuansa Cinta Akhwat Nusantara; Yeni Rosa Damayanti; Miranda Purdamasela; Ella Rosediana Putri; Muhammad Iqbal Malik; Mochammad Firmansyah Ramdhani (Lavish Opulent Education, 2024)
Human resource management (HRM) is a crucial aspect of the overall operations of a company or organization. HRM practices have a direct impact on the competitive advantage of a company and ensure the efficient use of human resources to achieve organizational goals. This research uses a literature study method based on previous research. The purpose of this study is to identify cross-cultural HRM practices between the Netherlands and South Africa. In the Netherlands, recruitment involves marketing through social media, while in South Africa, recruitment effectiveness is associated with knowledge and strategies to fill critical vacancies. Employee selection in the Netherlands tends to use psychological testing methods, while in South Africa, personality tests such as MBTI are more commonly used. Training and development in both countries involve efforts to improve employee skills, with an emphasis on life skills and adaptation to technological developments. The compensation system in the Netherlands focuses on non-monetary incentives, while in South Africa, compensation involves company policies that include knowledge utilization and strategic recruitment. Performance assessment in the Netherlands and South Africa is done through standards that include indicators of quality, accessibility, and cost of healthcare. This research provides deep insights into the differences in HRM practices across two different cultural contexts, enabling companies to understand hidden success factors and respond to future challenges with a more institutionalized approach.